Comparison Simulation Analysis of the Gradual Summation of a Function with Recognition of Direct Extrapolation Via IN Series - Stephanus Ivan Goenawan (International Journal of Applied Sciences and Smart Technologies, 2020)
A set of data pattern that have the characteristic of a function can be approached using Newton series simulation. When using the Newton series, the simulation result of the summation of extrapolation data can be gradually done in step by step. However, if using the IN series, the simulation result of the summation of extrapolation data doesnt need to be gradually done in step by step. The methodology in this research compares the data pattern from the simulation results of the high degree function with the results of interpolation and extrapolation from the results of the IN series simulation. Futhermore, will be carried out comparison simulation analysis of the summation of the function values gradually with the extrapolation function directly using the IN series. The result of comparison simulation analysis point out that the value of the total summation of data between the gradual and the direct summation is the same, so that the direct sum technique using the IN Series is able to make the total sum process more efficient.